การบริหารองค์การที่มีผลต่อการส่งมอบบริการสาธารณะของเทศบาลตำบล ในพื้นที่บริเวณชายแดนไทย-พม่า - โชติวรวัฒน์ ณัฐพัชร์ (Ph.D. in Social Sciences Journal, 2016)
ประชากรที่ใช้ในการวิจัยครั้งนี้ คือ ผู้บริหารของเทศบาลตำบลในพื้นที่บริเวณชายแดนไทย-พม่า ที่อยู่ใน 10 จังหวัดกลุ่มตัวอย่าง การวิจัยเชิงปริมาณ 410 คน และการวิจัยเชิงคุณภาพ 20 คน เครื่องมือ ที่ใช้ในการวิจัยเป็นแบบสอบถามและแบบสัมภาษณ์ที่ผู้วิจัยสร้างขึ้นโดยผ่านการตรวจสอบความแม่นตรง จากผู้ทรงคุณวุฒิ และทดสอบค่าความเชื่อมั่น .996 (a = 996)การวิเคราะห์ข้อมูลโดยใช้สถิติเชิงพรรณนา ค่าความถี่ ค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และสถิติเชิงอนุมาน การถดถอยเชิงพหุคูณ ผลการวิเคราะห์ข้อมูลโดยใช้สถิติการถดถอยเชิงพหุคูณ (multiple regression) พบว่า ปัจจัย สำคัญที่สามารถอธิบายคุณภาพการส่งมอบบริการสาธารณะของเทศบาลตำบลในพื้นที่บริเวณชายแดน ไทย-พม่า คือ ด้านวัฒนธรรมองค์การ ด้านกระบวนการ/เทคโนโลยี และด้านสมรรถนะทางการบริหาร ผลการวิจัยเชิงคุณภาพ ได้ทำการสัมภาษณ์ผู้นำชุมชน จำนวน 20 คน พบว่า 1) เทศบาล ตำบลควร กำหนดนโยบายที่มีเป้าหมายชัดเจนทั้งระยะสั้น ระยะกลาง และระยะยาว ครอบคลุมในด้านเศรษฐกิจ สังคม การเมือง การปกครอง และการศึกษาให้เกิดความยั่งยืน มีการเลือกแนวทางปฏิบัติได้ตรงกับวิสัย ทัศน์ พันธกิจขององค์การอย่างเป็นรูปธรรม สามารถถ่ายทอดให้กับบุคลากรนำไปสู่การปฏิบัติได้อย่างมี ประสิทธิภาพ 2) เทศบาลตำบลควรมีความพร้อมในด้านสถานที่ วัสดุ อุปกรณ์ บุคลากร และอื่น ๆ เพื่อนำ มาให้บริการสาธารณะได้อย่างมีประสิทธิภาพ มีจำนวนบุคลากรที่เพียงพอเหมาะสม มีการฝึกอบรมพัฒนา บุคลากรให้มีความรู้ ความสามารถในการปฏิบัติงานได้เป็นอย่างดี ใช้ระยะเวลาในการให้บริการสาธารณะ ได้อย่างเหมาะสม มีการแสวงหางบประมาณจากภายนอกองค์การเพื่อสนับสนุนการทำงานขององค์การ และ3) เทศบาลตำบลควรให้ความสำคัญกับการให้บริการสาธารณะที่มีความเสมอภาค ตรงกับความ ต้องการของประชาชน โดยคำนึงถึงประชาชนทุกกลุ่ม และควรมีการตรวจสอบการให้บริการสาธารณะ จากภาคประชาชนมากขึ้น Effects of Organizational Administration on Service Delivery of Sub-District Municipalities in Areas along the Thai- Myanmar Border The population used in this study was chairmen of the sub-district municipalities of ten provinces The samples for quantitative research were 410 officials and for qualitative research, 20 local leaders. The instrumentation and equipment used in the sampling and interviews were created and already checked for this accuracy and validity by the experts and confidence test 0.991 (a = .991). The data obtained were then analyzed using descriptive statistics, frequency, percentage, average, standard deviation, and inferential multiple regression analysis. The stepwise multiple regression revealed that the independent variables which influenced the public service delivery of the aforesaid municipalities included organization culture, process/technology, and managerial competency, respectively. From the interviews of 20 local leaders and on a qualitative research basis, it was found that: (1) the sub-district municipalities should have clear goals both short term and long term. comprehensive economic, social, political and educational sustainability. choosing a course of action to meet the vision. the mission of the organization is substantial. transfer to the staff to perform effectively. 2) the sub-district municipalities should be ready in the personnel, equipment and other property. in order to serve the public more effectively. an adequate number of personnel. training and knowledge development. ability to work well. the duration of the public service properly. the pursuit of external funding to support the work of organizations spend time in public services properly. and 3) the sub-district municipalities should give priority to the provision of public services are equal. meet the needs of the people. with regard to people of all groups. and should be checked by the public services of the public sector.